Enhancing Student's Skills: Need Analysis To Develop E-Modul Integrated Problem-Based Learning Model On Smartphone-Based - Melfa Rahmayani; Asrizal Asrizal (Department of Physics Universitas Negeri Padang, 2023)
The development of Science and Technology is a feature of the 21st century which requires students to have critical thinking, creative thinking, communication, and collaboration skills. This study aims to need analysis to develop an e-module for a renewable energy-integrated PBL model based on a smartphone to improve students' creative thinking and communication skills. The objects of this study were three high school physics teachers, 70 class X high school students, and teacher documents in the form of learning objectives, teaching modules, and documents on the student's midterm assessment results. Data collection techniques used in this study were questionnaires, documentation, and tests of student's creative thinking and communication skills. Data collected were analyzed using quantitative descriptive statistical analysis techniques. Based on data analysis, the study results include: 1) the use of ICT in physics learning is in the sufficient category, this is not in line with the significant potential use of technology in schools, especially the use of smartphones, 2) students characteristics seen from the components of background, interest in learning, learning motivation, learning styles, and students' attitudes are in a good category, but the value of knowledge and creative thinking skills and students' communication is still low, 3) the learning objectives carried out by the teacher as seen from the flow analysis of the learning objectives of three teachers are in the category sufficient, 4) the learning arrangements carried out by the teacher by looking at the teaching modules of three teachers are in the sufficient category